The Effect of Gender-Based Project Based Learning (PJBL) Ecomedia Pop Up Book Learning Model on Sociology Subject Learning Outcomes - Yustiani, Martyas; Taufiqulloh, Taufiqulloh; Muljani, Sutji (Journal of English Language and Education, 2025)
This study focuses on efforts to improve student learning outcomes in the subject of Sociology at SMA Negeri 1 Slawi. It was found that student learning outcomes were still suboptimal, attributed to a lack of variation in teaching methods, minimal active student engagement, and limited learning media. To address these issues, the study implemented a Project Based Learning (PjBL) model based on ecomedia. Using a quantitative method and factorial design, the research involved 72 tenth-grade students, with class X.9 serving as the experimental group and class X.8 as the control group. Through the analysis of pre-test and post-test scores, the study evaluated the differences in learning outcomes before and after the implementation of the PjBL model. The results indicated that the ecomedia-based PjBL model had a significant positive impact on student learning outcomes for both male and female students, with no notable differences between the two. These findings highlight the importance of developing teaching methods that combine conventional elements with PjBL, as well as encouraging teachers to be more creative in utilizing learning media to make the teaching and learning process more engaging and effective for students.